2021
DOI: 10.3897/pharmacia.68.e68291
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Ifosfamide to nanoemulsion-based clove oil enhances its toxicity on malignant breast cancer and cervical cancer cells

Abstract: The anticancer effects of chemotherapeutic agents may be accentuated, and their side effects minimized by combining them with essential oils in nanocarrier systems. This study aimed to incorporate ifosfamide (IF) into nanoemulsion-based clove oil (IF-CLV). The nano-emulsion (NE) formulas were characterized with Zetasizer. The cytotoxicity of the formulated NEs against cervical (HeLa) and breast (MCF-7) cancer cell lines was determined using MTT assay, light microscopy, and DAPI staining. The z – average diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…When compared with Oxa-NS treated group, the combined formulation caused a 109.8-fold reduction in the dose of Oxa needed for 50% growth inhibition, relative to HT-29 cells treated Oxa-NS ( p ≥ 0.05). This observation could be attributed to the enhancement of the penetration of chemotherapeutics through the cell membrane when delivered into nano-formulations, in addition to the cytotoxic potential of essential oils on cancer (Al-otaibi, 2021 ; Zhang et al., 2019 ; AlMotwaa, 2021 ; Al-Otaibi et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared with Oxa-NS treated group, the combined formulation caused a 109.8-fold reduction in the dose of Oxa needed for 50% growth inhibition, relative to HT-29 cells treated Oxa-NS ( p ≥ 0.05). This observation could be attributed to the enhancement of the penetration of chemotherapeutics through the cell membrane when delivered into nano-formulations, in addition to the cytotoxic potential of essential oils on cancer (Al-otaibi, 2021 ; Zhang et al., 2019 ; AlMotwaa, 2021 ; Al-Otaibi et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The marked elevations in ROS levels in cells treated with Oxa + TPO-NANO and TPO-NANO, relative to cells treated with Oxa-NS might be explained by the apoptotic potential of these two formulations on the studied cancer cells. Previous studies have demonstrated the anticancer potential of essential oils formulated into nanocarriers which predominantly triggered ROS production within cancer cells, thereby facilitating apoptosis of the treated cells (Al-otaibi, 2021 ; AlMotwaa, 2021 ; Salehi et al., 2020 ; Panyajai et al., 2022 ; Nirmala et al., 2020 ). Furthermore, TPO and its bioactive components have been shown to exert anticancer potential predominantly by induction of ROS generation and induction of cell death through the mitochondria-mediated apoptotic pathway (Su et al., 2013 ; Bai & Tang, 2020 ; Li et al., 2013 ; Sobral et al., 2014 ; Pan et al., 2016 ; Karan et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The average of droplet size of the PC-NE loaded with GEM (PC-NE:GEM) was 11.36 ± 0.0.21 nm, with a PDI of 0.010 ± 0.003 ( Figure 4 ). The droplet size was increased because of the GEM loading [ 30 , 31 ]. A lower PDI value indicates more uniform droplet size [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further, the levels of IL-6 and IL-8 went down because the NF-B signaling pathway was turned off. This stopped the p50 and p65 subunits from being phosphorylated and moved them to the nucleus [ 203 ].…”
Section: Breast Cancermentioning
confidence: 99%